Biomass as energy source : resources, systems and applications - Dahlquist, Erik. (Leiden, The Netherlands : CRC Press/Balkema, 2013)
'Providing a state of the art in the field of available and future biomass resources, energy systems using biomass and optimization and control of systems and processes. The book covers biomass resources globally, but also complex systems such as biorefineries, polygeneration and pulp and paper industry, as well as chemicals used as feedstocks for plastics. Other examples are using wood for textiles and food additives as nano-fibers. The contributing authors are highly-qualified researchers and engineers in different aspects of biomass utilization from most parts of the world'--
Includes bibliographical references and index.
Keywords: Biomass energy